Sustainability Reporting, Directors’ Ownership, and Financial Performance of Listed Manufacturing Firms in Africa - Emmanuel Kwame Doffour; Anthony Adu-Asare Idun; Isaac Kwadwo Anim; Emmanuel Boye Asamoah; Maya Novitasari (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study examines how directors’ ownership moderates the relationship between sustainability reporting and the financial performance of manufacturing companies listed in Africa. This study used corporate reports from 2015 to 2021 for secondary data and conducted Regression analysis in Stata 15 with GMM as the estimator. Without the moderating variable, sustainability reporting had a negative impact on all financial performance indicators. Introducing directors’ ownership as the moderating variable, the interaction had a negative role in the relationship between sustainability reporting and financial performance metrics. However, the interaction changed the negative effect of sustainability reporting on management’s perspective (ROA) and market perspective (TQ) of financial performance from negative to positive. The study provides insight into how sustainability is reported in Africa, building on previous literature and expanding research to include manufacturing companies in Africa. Also, the study shows how directors having more ownership stake in the firm influence their sustainability reporting and performance. This study in Africa, unlike previous research, analyses how directors’ ownership influences the relationship between sustainability reporting and financial performance and finds evidence against the convergence of interest hypothesis.